Análisis comparativo entre red de computadoras tradicional y red definida por software: caso de estudio ESPAM MFL - Alcívar Marcillo, Pedro Antonio (2019)
Computer networks are one of the technologies that have experienced very few significant changes since their invention. This statement is based on the fact that protocols established more than 25 years ago are still valid. For this reason, the goal of this work was to compare, the traditional network paradigm against the software-defined network model (SDN) in a local area network environment which had common services for a higher education institution, to determine the applicability of this last paradigm in the analyzed environment. Two simulation environments were implemented, a traditional network, based on the ESPAM MFL’s sector 8 network, and an SDN with a similar design, but with the proper characteristics of this paradigm. The environments were implemented in the GNS3 network simulator. For add the services such as web server and virtual classroom, VirtualBox and VMware were integrated into the simulator. To obtain the results, virtual machines were implemented in the simulator, which consulted the local and external services. From these tests, the latency, jitter, and packet loss were obtained by Smokeping network monitoring application. Based on the results of both paradigms, it was determined that SDN has the advantage of requiring fewer connection devices, as well as the results in terms of performance, control, and administration of the network favor the implementation of this model in similar environments.